Implementasi Metode SMART (Simple Multi Attribute Rating Technique) Pada Sistem Pendukung Keputusan Pemberian Kredit Pinjaman - Wildan Muhammad Ardana; Irma Rofni Wulandari; Yuli Astuti; Lilis Dwi Farida; Wiwi Widayani (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2022)
Koperasi Simpan Pinjam (KSP) Tamanmartani Sejahtera is an operational savings and loan cooperative that utilizes funds from members in the form of savings and then flows back to members in the form of credit or loans. KSP Tamanmartani Sejahtera's main problem is arrears or customer credit payment delays. If it is allowed to continue, it will make it difficult for cooperatives to develop. One way to reduce delays in credit payments is to select prospective customers selectively. When choosing prospective customers, managers often experience difficulty making credit request decisions. Managers must consider and analyze the background of the credit application. The provision of credit to prospective customers must meet the standard criteria the cooperative sets. Based on these problems, to provide maximum recognition, it is necessary to have a system to help managers determine customer credit decisions. A Decision Support System (DSS) is a system that can provide information and manipulation data to assist decision-makers. One can use many choices, one of which is the Simple Multi-Attribute Rating Technique (SMART). The SMART method can help solve complex problems based on the difficulties encountered in KSP Tamanmartani Sejahtera. The results of this study are The SMART method was successfully implemented into a website-based system and displayed the ranking of customers who deserved to be given a loan. The test results with Black Box testing show the system can run according to a predetermined design.